The effects of propranolol on heart rate variability and quantitative, mechanistic, pain profiling: a randomized placebo-controlled crossover study - Petersen, Kristian Kjær; Koenig, Julian (Scandinavian journal of pain, 2018)
Abstract Background and aims The autonomic nervous system (ANS) is capable of modulating pain. Aberrations in heart rate variability (HRV), reflective of ANS activity, are associated with experimental pain sensitivity, chronic pain, and more recently, pain modulatory mechanisms but the underlying mechanisms are still unclear. HRV is lowered during experimental pain as well as in chronic pain conditions and HRV can be increased by propranolol, which is a non-selective β-blocker. Sensitization of central pain pathways have been observed in several chronic pain conditions and human mechanistic pain biomarkers for these central pain pathways include temporal summation of pain (TSP) and conditioned pain modulation (CPM). The current study aimed to investigate the effect of the β-blocker propranolol, and subsequently assessing the response to standardized, quantitative, mechanistic pain biomarkers.
Gesehen am 21.04.2020